THE DEVELOPMENT OF PERFORMANCE EFFICIENCY OF AUGMENTED REALITY TECHNOLOGY FOR TOURIST ATTRACTIONS IN THE WELLNESS TOURISM ROUTE, RANONG PROVINCE - Tubchai, Komsun; Junng, Parichart; Srisuwan, Passakorn (Journal of Liberal Art of Rajamangala University of Technology Suvarnabhumi, 2025)
This article aimed to 1) develop augmented reality technology for tourist attractions in the wellness tourism route, Ranong Province, to enhance the tourists’ awareness through the use of augmented reality technology, 2) evaluate the level of acceptance of augmented reality technology in the wellness tourism route, Ranong Province, and 3) distribute information and augmented reality technology to the tourist attraction owners. The study employed 1) the augmented reality technology of tourist attractions in Ranong wellness tourism, 2) the augmented reality technology quality survey, 3) the augmented reality technology satisfaction survey, and 4) the knowledge achievement test. Using Taro Yamane's formula, a sample of 400 tourists was selected from the population of tourists who visited Ranong. 1) The three media outlets evaluated the quality of augmented reality technology. The average rating for specialists was at 4.53, marking the highest level and surpassing the established criteria. 2) The overall satisfaction of a sample of four hundred tourists who experienced augmented reality technology was exceptionally high, with an average rating of 4.50. 3) The achievement results of tourist attraction owners before and after training were at 13.33, surpassing the pre-training results and meeting the statistically significant 0.1 threshold. This indicated that augmented reality technology had the potential to motivate and influence the acceptance of wellness tourism among Ranong tourists.